Impact of dry rice grain packing density and time on the performance of two stage dehumidifier - Shiva Kumar; Sampath Suranjan Salins; Uday Krishna Kuroor; Sloane Winslow D’Souza; Anupam Bose (Scientific Reports)
Abstract This study presents the design and development of a multistage solid desiccant dehumidifier using rice grains as the desiccant material. The rice packing densities varied between 1100 and 4390 kg/m3, and experiments were conducted to assess performance over different time intervals. Results indicated that system performance improved with increasing packing density up to 3290 kg/m3, after which a decline was observed. Additionally, performance improved with time, stabilizing after approximately 15 min of operation. The system achieved a maximum moisture removal rate of 0.18 g/s, a dehumidification efficiency of 73.57%, a coefficient of performance (COP) of 4.35, and a mass transfer coefficient of 20.40 kg/m2·s. The highest dehumidification efficiency was recorded in the first stage, with a notable reduction in the second stage. Velocity reductions from top to bottom for packing densities of 1100 kg/m3, 2190 kg/m3, 3290 kg/m3, and 4390 kg/m3 were 25%, 38.88%, 51.51%, and 66.66%, respectively. While the exhaust air met ASHRAE thermal comfort standards, an increased pressure drop was observed, with a maximum value of 180 Pa recorded.